Uzbekistan's transformation : strategies and perspectives - Schmitz, Andrea (2020)
Zusammenfassung: The presidential transition in Uzbekistan represents a novel development in the post-Soviet space. Regime insider Shavkat Mirziyoyev has succeeded in initiating change without provoking destabilisation. His reform programme aims to liberalise the economy and society while leaving the political system largely untouched. Implementation is centrally controlled and managed, in line with the country’s long history of state planning. Uzbeks accept painful adjustments in the expectation of a rising standard of living. And the economic reforms are rapidly creating incontrovertible facts on the ground. Uzbekistan has also made significant moves towards political liberalisation, but remains an authoritarian state whose institutional framework and presidential system are not up for discussion. Rather than democratisation, the outcome of the transformation is more likely to be "enlightened authoritarianism" backed by an alliance of old and new elites. Nevertheless, there are good reasons for Germany and Europe to support the reforms. Priority should be placed on the areas most relevant for fostering an open society: promoting political competition, encouraging open debate, fostering independent public engagement and enabling genuine participation